Efficient Management of Agro-Industry Cluster - E. Kuldashev; M. Makhmudov (Zien Journals, 2023)
This article shows ways to effectively manage an agro-industry cluster. Effective management of agroindustry cluster is based on digital management
Keywords: Cluster; agro-industry; digital management; efficient